2020
DOI: 10.1177/1060028020903816
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evaluation of Dosing in Patients Converted From Insulin Glargine (Lantus) to Insulin Glargine (Basaglar)

Abstract: Background: Basaglar, insulin glargine (BGlar; Eli Lilly, Indianapolis, IN), a follow-on biologic, was developed after the patent for Lantus, insulin glargine (LGlar; Sanofi-Aventis, Paris, France) expired. Objective: To compare the dosing and hemoglobin A1C (A1C)-lowering effects of BGlar compared with LGlar in a real-world setting. Methods: Adult patients, at 5 clinics, with type 1 (T1DM) or type 2 diabetes mellitus (T2DM) who were converted from LGlar to BGlar were included in this retrospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…In contrary to our results, Pitlick et al (29) conducted a retrospective observational study including adult patients with type 1 or 2 DM who were changed from Lantus (LGlar) to insulin glargine (BGlar) at five clinics. They showed that the findings of this retrospective analysis indicate that BGlar produced comparable glycemic outcomes in a real-world scenario when compared to LGlar, and that it would be a better alternative in a value-based health care system.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrary to our results, Pitlick et al (29) conducted a retrospective observational study including adult patients with type 1 or 2 DM who were changed from Lantus (LGlar) to insulin glargine (BGlar) at five clinics. They showed that the findings of this retrospective analysis indicate that BGlar produced comparable glycemic outcomes in a real-world scenario when compared to LGlar, and that it would be a better alternative in a value-based health care system.…”
Section: Discussioncontrasting
confidence: 99%
“…Change in HbA1c for Basaglar and Lantus was −1.29% and −1.34% from baseline to 6 months, respectively, in the trial, and we observed similar magnitude of reduction in our study 11 . One real‐world study in the United States examined the HbA1c‐lowering effect of Basaglar compared with Lantus among 225 patients with type 1 diabetes or type 2 diabetes who converted from Lantus to Basaglar 21 . At 3 and 12 months postconversion, the authors found no significant differences in change of HbA1c, while also reporting that the monthly acquisition cost of Basaglar was significantly less at conversion date (16% less, $286 vs. $341, P < .001) and 6 months (17% less, $290 vs. $351, P < .001).…”
Section: Discussionsupporting
confidence: 75%
“…Basaglar ® , which is a biosimilar insulin glargine of the reference biologic (Lantus ® ), has shown comparable safety and efficacy profiles to Lantus ® among patients with type 1 and type 2 diabetes in different industry–sponsored randomized clinical trials ( 24 , 25 ). Moreover, a recently published study that examined the interchangeability between Basaglar ® and Lantus ® in real–world settings found no difference in the glycemic outcomes among the 225 adult patients who were retrospectively recruited from five clinics affiliated with three different healthcare systems in the United States ( 27 ). Similar findings were observed in this study since no difference in the A1C levels was found between the baseline (e.g., before Basaglar ® treatment) and after 12 months of follow–up.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some observational studies have shown no difference in terms of a change in the glycated hemoglobin levels (A1C) or daily insulin units. Moreover, the switch from Lantus to Basaglar resulted in significant cost savings according to a recently published retrospective observational study that included 225 patients from five different clinics affiliated with three different healthcare systems in the State of Iowa, United States ( 27 ).…”
Section: Introductionmentioning
confidence: 99%